A blooming interest in the hydraulic traits of flowers. (21st June 2018) - Gleason, Sean M.
Abstract : This article comments on :Water relations of Calycanthus flowers: Hydraulic conductance, capacitance, and embolism resistance Abstract : This article comments on :Water relations of Calycanthus flowers: Hydraulic conductance, capacitance, and embolism resistance